The visual identity of science communication journals: a comparative study of periodical covers in Ibero-American publications indexed in Scopus - González-Díez, Laura; Puebla-Martínez, Belén; Sánchez-Pita, Fernando (InfoDesign, 2026)
This article aims to analyse the current trends of design regarding the covers of science communication journals in Ibero-America, focusing specifically on those indexed in Scopus. From a perspective that acknowledges the relevance of visual aspects in relation to editorial identity, the study examines the formal design decisions underlying the graphic presentation of these publications. To this end, a descriptive content analysis was conducted with a sample of 64 journals using a coding system comprised of variables related to identification, design, and content. The findings indicate a preference for functional and homogeneous visual models, characterised by symmetrical compositions, a predominance of sans serif typeface, and the moderate use of colour. Although images play a key role in more than half the covers, they tend to be institutional in nature, with a scarce amount of vivid experimentation. Similarly, there is limited typographic diversity and only slight variability from one issue to another, resulting in visual identities that are quite similar to each other. These trends highlight the need to strengthen editorial design as a strategic tool for improving the visibility, consistency, and graphic identity of science communication journals.
A identidade visual de revistas científicas: um estudo comparativo de capas de publicações ibero-americanas indexadas na Scopus
Este artigo tem como objetivo analisar as tendências atuais de design nas capas de revistas científicas na Ibero-América, com foco específico naquelas indexadas na Scopus. A partir de uma perspectiva que reconhece a relevância dos aspectos visuais para a identidade editorial, o estudo examina as decisões formais de design subjacentes à apresentação gráfica dessas publicações. Para isso, realizou-se uma análise de conteúdo descritiva com uma amostra de 64 periódicos, utilizando um sistema de codificação composto por variáveis relacionadas à identificação, ao design e ao conteúdo. Os resultados indicam uma preferência por modelos visuais funcionais e homogêneos, caracterizados por composições simétricas, predominância de tipos sem serifa e uso moderado de cor. Embora as imagens desempenhem um papel central em mais da metade das capas, elas tendem a ter caráter institucional, com pouca experimentação visual mais expressiva. Da mesma forma, observa-se limitada diversidade tipográfica e baixa variabilidade entre edições, resultando em identidades visuais bastante semelhantes entre si. Essas tendências evidenciam a necessidade de fortalecer o design editorial como ferramenta estratégica para aprimorar a visibilidade, a consistência e a identidade gráfica das revistas científicas.
Keywords: editorial design; scientific journals; visual identity; scientific communication; Scopus; design editorial; revistas científicas; identidade visual; comunicação científica